Novel 2,6-disubstituted pyridine hydrazones: Synthesis, anticancer activity, docking studies and effects on caspase-3-mediated apoptosis - TÜRE, ASLI; KÜÇÜKGÜZEL, İLKAY; ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (ELSEVIER, 2021)
Novel pyridine-based dihydrazones (3a-l) were synthesized by the condensation of appropriate aldehydes and pyridine-2,6-dicarbohydrazide (2) which was obtained by the treatment of dimethyl pyridine-2,6-dicarboxylate (1) with hydrazine hydrate. Structures of all the synthesized compounds were supported by their FTIR, H-1 NMR, C-13 NMR and microanalytical data. The compounds were screened primarily for their antibacterial activities as well as anticancer activities. None of the synthesized compounds had important antibacterial activity. Among the compounds which were tested against human colon cancer cell line (HT-29), compounds 3f and 3k showed significant activity (IC50=6.78 mu M for compound 3f, IC50 = 8.88 mu M for compound 3k). In addition, compound 3g exhibited promising activity against Ishikawa human endometrial cancer cell line (ISH) with an IC50 value of 8.26 mu M. At 10 mu M, compounds 3f, 3k and 3g caused morphological changes of HT-29 and ISH cells and caspase-3 activation. In addition, these compounds were evaluated against NIH 3T3 mouse embriyonic fibroblast cell line and all synthesized compounds (3a-l) were found to be less toxic than paclitaxel. Moreover, possible inhibition mechanism of compound 3g was evaluated in silico against BRAF kinase enzyme. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: 2,6-Disubstituted pyridine; Hydrazone; BRAF; Apoptosis; Anticancer; Molecular modeling; BIOLOGICAL-ACTIVITIES; HYDRAZIDE-HYDRAZONES; ENDOMETRIAL CANCER; DERIVATIVES; RISK; BRAF; RAF